(3JMQjQ cJGH GQSWQNS aj LQej GdfjQjf hHYOgeGs - (3GQSWQNSs
(3ChdgG (B:s
(3HYO GdOjHGLI UOQ GdcJGH fVY Cf GdbeQ jbHd GdVhA ef GdTeS hEf bOQ GdCQV YfO adc GcHQ GdHQhL bOQ GdeQcR hGdfbWI EPG XgQ dfG GdbeQ efJUa aj GdVhA s
(3BNQgG (B:s
(3hHGdJaUjd fSHI M W Edi W H GUZQ ef fSHI CYfj ef fSHI Zdi GdhGMO hPdc CQOfGg s
(3Vef eLehY , JQJjHgG (B: 9s
(3jTJed (B17 (3TcdGs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdj (B(1930) s
Keywords: (3eJaQbGJs